UPAYA PENINGKATAN KEMAMPUAN GURU-GURU DALAM PENGUASAAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING DENGAN PERAN PENDAMPINGAN PENGAWAS DI SD NEGERI NO. 164518 TEBING TINGGI - Marice Sirait (PGSD Universitas Negeri Medan, 2018)
The research was carried out by supervisors on target teachers at SD Negeri No. 164518 Tebing Tinggi. Research into the form of school action consists of two cycles for three months. The instruments used were observation, interviews and description tests. Research respondents for several types of subject teachers were 31 people who varied the background of the participants. The purpose of the study was to find out through the supervisory role of providing assistance in mastering the Contextual Teaching and Learning (CTL) learning model. In addition, so that teachers are accustomed to developing students' potential in learning. Assistance strategy for supervisors through modeling, simulating fellow teachers alternately. The initial test of the teacher's ability to master the learning model is relatively low with an average of 48.06% increasing after mentoring to 69.55% in the first cycle, then evaluating the teacher's ability in the second cycle increased to 79.68%. The mastery of teacher knowledge at the end of the second cycle after being evaluated by a 10 item description test reached 90% with completeness of 31 people in the group above 70%.Keywords: Contextual Teaching And Learning, Companion Role